Konstruksi Keilmuan Balaghoh: Sebuah Tinjauan Dari Perspektif Filsafat Ilmu - Mohammad ‘Ainul Fikri Mahmudi; M. Yunus Abu Bakar (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
The purpose of this study is to examine the scientific construction of Ilmu Balaghoh or Arabic rhetoric using the philosophy of science approach. Ilmu Balaghoh is a crucial discipline in Islamic scholarship that explores the beauty, meaning, and power of language, particularly concerning the articulation of the beauty and meaning of Qur'anic texts. The philosophy of Ilmu Balaghoh provides a new perspective on its ontological, epistemological, and axiological dimensions. This research employs a qualitative method through literature analysis, utilizing both primary and secondary sources, including references on Balaghoh and the philosophy of science. The findings reveal that Balaghoh is not merely about language but possesses philosophical absorption as an approach to constructing sentences that convey meaning and messages aesthetically. The ontology of Ilmu Balaghoh pertains to the essence of language as a medium of divine and human communication, while its epistemology lies in analogical and deductive methods to generate knowledge. The axiology of Balaghoh focuses on the development of communication ethics and rhetoric in Islamic studies. Based on the research results, it can be concluded that Ilmu Balaghoh is a complex and integral discipline that enriches the study of language and values in Islam. This study is expected to serve as a foundational framework for the development of Ilmu Balaghoh in the context of contemporary and interdisciplinary studies.